Pengaruh Kompres Hangat terhadap Nyeri Punggung Ibu Hamil Trimester III di Puskesmas Sekernan Ilir Tahun 2020 - Yuli Suryanti; Dewi Nopiska Lilis; Harpikriati Harpikriati (Universitas Baiturrahim, 2021)
Introduction Back pain is the most common complaint with a prevalence rate of 49%. Back pain that is not immediately treated, can cause long-term back pain, increase the tendency of post-partum back pain and chronic back pain that will be more difficult to treat or cure, that is, when the pain spreads to the pelvic region which causes difficulty walking and thus requires crutches or assistive devices. other way. PURPOSEQuantitative research with quasi-experimental design with one group pretest-posttest to determine the effect of Warm Compresses on Back Pain of Trimester III Pregnant Women in SekernanIlir Health Center in 2020. Methodsthe population is all Trimester III pregnant women in the work area of SekernanIlir Health Center up to January 2020 which totaling 296 people. Samples were 30 respondents. This research was conducted from January to March 2020. ResultsData analysis was carried out univariate and bivariate. The result of univariate analysis before giving a warm compress is moderate pain. The results of bivariate analysis showed that there was an effect of warm compresses on the level of back pain in third trimester pregnant women and p-value = 0.000 (p <0.05). conclusionit is expected that the Puskesmas will provide knowledge to pregnant women about ways to reduce back pain in third trimester pregnant women, in addition to pharmacological treatment, it can also be done with non-pharmacological treatment, namely warm compresses